2007
DOI: 10.1016/j.rmed.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and lung function in 30-year-old individuals with alpha-1-antitrypsin deficiency

Abstract: At the age of 30, the AAT-deficient individuals in this cohort report more symptoms than the control subjects. Smoking is less common in the cohort compared to controls. Their lung function is normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
1
40
0
5
Order By: Relevance
“…[11][12][13][14] Three studies reported that providing information on AATD status to individuals identified at birth through neonatal screening programs reduced smoking rates in these individuals. In the first study adolescents with AATD identified at birth had a significantly lower current and previous smoking rate compared with matched control subjects (current smoking rate: 6% vs 17%, P < .05; previous smoking rate: 6% vs 19%, P < .05).…”
Section: Importance Of Early Diagnosismentioning
confidence: 99%
“…[11][12][13][14] Three studies reported that providing information on AATD status to individuals identified at birth through neonatal screening programs reduced smoking rates in these individuals. In the first study adolescents with AATD identified at birth had a significantly lower current and previous smoking rate compared with matched control subjects (current smoking rate: 6% vs 17%, P < .05; previous smoking rate: 6% vs 19%, P < .05).…”
Section: Importance Of Early Diagnosismentioning
confidence: 99%
“…The maximum FEV 1 % predicted is not known for each individual; in order to include only positive values, the maximum observed FEV 1 % predicted in our cohort (140% predicted) was used in the numerator for all subjects. The age of initiation of FEV 1 decline is also unknown in this cohort, but Piitulainen and colleagues have demonstrated that PI Z individuals typically have normal FEV 1 values at least until age 30 [Bernspang et al, 2007]. Thus, we selected ages 20, 25, and 30 as age thresholds for the initiation of FEV 1 decline.…”
Section: Cohort and Phenotype Definitionmentioning
confidence: 99%
“…Severe AATD is characterised by low levels of A 1 -PI in blood and tissues and can lead to liver disease (cirrhosis or hepatocellular carcinoma), caused by aggregation of misfolded A 1 -PI as polymers in hepatocytes, and/or chronically progressing lung disease, including emphysema, as a result of uncontrolled degradation of lung tissue by proteases, mainly neutrophil elastase (NE) (2,3). Severe AATD presents with pulmonary symptoms, often including coughing, wheezing, shortness of breath and recurrent respiratory tract infections that are similar to those observed in typical chronic obstructive pulmonary disease (COPD) (4)(5)(6). Whilst the pathomechanism of AATD-related COPD is distinct from COPD per se, recent evidence suggests that in both emphysema is a major contributor (7,8).…”
Section: Introductionmentioning
confidence: 99%